Profile and outcome of pregnancy with congenital heart diseases: a retrospective study from a South Indian tertiary care hospital - S., Mamatha; L., Hemapriya; M., Mahesh; M., Madhumitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Women with congenital heart disease who become pregnant form an important subgroup of pregnancy cardiac disorders. The additional stress of pregnancy represents a further challenge. Methods: This was a retrospective study. Patient records between 2011and 2015 pertaining to 77 pregnant women with congenital heart diseases were analysed. Results: There was only one patient aged more than 35 years. The age of the others ranged from 18 to 35 years. The mean age was 24 years. There was a slight rural preponderance with 43 (55.8%) from rural areas. Majority 49 (63.5%) belonged to lower middle socioeconomic status. 71 (92.2%) had NYHA functional Class I. Two patients of Class II had worsening of their status. There were no cases of Atrial Fibrillation and only 2(2.6%) had CCF.ASD closure was the commonest procedure done24 (31.2%). There were 6 (7.8%)cases of device closure of PDA and no cases of VSD. Anemia and GDM were seen in 4 (5.2%). The commonest period of gestation at delivery was 37-40 in 64 (83.1%). ASD was the commonest type of lesion 42 (54.5%). 36 (46.8%) had spontaneous labour and there were 18 23.4%)caesarians. Previous LSCS was the commonest indication for LSCS. Full term normal vaginal delivery was seen in 45 (88.2%). Majority of the newborns 30 (39%) had a birth weight in the range 2.6-3.0 kgs. Conclusions: There is a significant burden of Heart disease with pregnancy afflicting young rural women and those from lower socioeconomic levels. Higher level of specialised care minimizes poor maternal and fetal outcomes.